1996
DOI: 10.1007/bf02359383
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and neurotransmitter regulation of GnRH gene expression and related reproductive behaviors

Abstract: Gonadotropin-releasing hormone (GnRH), having a highly conserved structure across mammalian species, plays a pivotal role in the control of the neuroendocrine events and the inherent sexual behaviors essential for reproductive function. Recent advances in molecular genetic technology have contributed greatly to the investigation of several aspects of GnRH physiology, particularly steroid hormone and neurotransmitter regulation of GnRH gene expression. Behavioral studies have focused on the actions of GnRH in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 360 publications
(416 reference statements)
3
45
0
Order By: Relevance
“…A similar decrease in GnRH mRNA levels has been reported in the rat (24,25), although this finding is controversial (reviewed in Ref. 21). Other researchers found no effect (26) or an increase (27) in GnRH mRNA levels after ovariectomy in female rats.…”
Section: Species Comparisonssupporting
confidence: 62%
See 1 more Smart Citation
“…A similar decrease in GnRH mRNA levels has been reported in the rat (24,25), although this finding is controversial (reviewed in Ref. 21). Other researchers found no effect (26) or an increase (27) in GnRH mRNA levels after ovariectomy in female rats.…”
Section: Species Comparisonssupporting
confidence: 62%
“…In the rat, however, in those studies in which changes were reported (reviewed in Ref. 21), increases in either cellular GnRH mRNA levels or GnRH mRNA cell numbers occurred in the organum vasculosum of the lamina terminalis/rostral preoptic area during the estrogen-induced LH surge (10,15,22,23). There is a species difference in the temporal relationship between the changes observed in GnRH mRNA levels and the LH surge.…”
Section: Species Comparisonsmentioning
confidence: 96%
“…These data agree with results for the rat (66,115,139,235), which also failed to detect any significant changes in hypothalamic GnRH mRNA levels after steroidal manipulations. By contrast, there are also numerous reports (reviewed in 83,190) showing either increases or decreases in POA GnRH mRNA levels after gonadectomy in rats, although these changes in GnRH mRNA levels are relatively small compared to the amount of LH released following gonadectomy. Thus, the postgonadectomy rise in LH does not seem to depend on dramatic increases in hypothalamic GnRH gene transcription in either rats or ferrets.…”
Section: Gnrh Biosynthesismentioning
confidence: 96%
“…Numerous studies (reviewed in 83,190) have been conducted in spontaneously ovulating species, including rats and sheep, to determine whether the steroid-induced preovulatory release of GnRH depends, in part, on increased GnRH gene transcription in POA neurons. Unfortunately, results obtained in these studies have been inconclusive.…”
Section: Neuronal Fos/gnrh Colocalizationmentioning
confidence: 99%
“…Furthermore, basal levels of LH were elevated in peripubertal females 3 weeks after ovariectomy and these animals were more responsive to steroid-induced LH secretion. One possible explanation for these results is that as the interval between ovariectomy and steroid replacement increased, circulating levels of gonadotropins increased due to loss of negative feedback (Sagrillo et al 1996, Gore & Roberts 1997, Herbison 1998). Loss of negative feedback causes the pituitary to be more responsive to GnRH stimulation (Legan et al 1973) and results in increased LH release following steroid hormone treatment.…”
Section: Discussionmentioning
confidence: 99%